2008
DOI: 10.2319/0003-3219(2008)078[0631:cigsab]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Change in Grafted Secondary Alveolar Bone in Patients with UCLP and UCLA

Abstract: Overpacking and/or excessive condensation of the grafted bone is not necessary in UCLA with the lingual process because of the greater chance of resorption on the labial side of the grafted bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
2
29
0
8
Order By: Relevance
“…Os resultados mostraram que as imagens 2D e 3D de caninos superiores impactados podem produzir diferentes diagnósticos e tratamentos, havendo uma confiança maior dos profissionais na exatidão da TCFC 11 . Para o planejamento individual, as imagens 2D não são confiáveis em todos os casos, sendo essencial a análise tridimensional (3D) por pontos de referência, linhas e planos (18,22) . Em nossa pesquisa, também foi observado melhor resultado na correlação entre a radiografia periapical, que é responsável por essa visualização do suporte ósseo do dente adjacente à fissura, com resultados muito próximos aos da TCFC.…”
Section: Resultados Discussãounclassified
“…Os resultados mostraram que as imagens 2D e 3D de caninos superiores impactados podem produzir diferentes diagnósticos e tratamentos, havendo uma confiança maior dos profissionais na exatidão da TCFC 11 . Para o planejamento individual, as imagens 2D não são confiáveis em todos os casos, sendo essencial a análise tridimensional (3D) por pontos de referência, linhas e planos (18,22) . Em nossa pesquisa, também foi observado melhor resultado na correlação entre a radiografia periapical, que é responsável por essa visualização do suporte ósseo do dente adjacente à fissura, com resultados muito próximos aos da TCFC.…”
Section: Resultados Discussãounclassified
“…8 Moreover, 2 dimensional (2D) imaging is too limited in volume analysis due to the superimposition of the adjacent anatomical structures, distortions and enlargements. [9][10][11][12] Therefore the use of CT in the assessment of the alveolar bone graft is recently widespread. 10,11,13,14 The common point of agreement between these studies is that the amount of bone loss is significantly higher than that shown by 2D imaging.…”
Section: Discussionmentioning
confidence: 99%
“…7 In early stages of cleft palate repair, bone grafts are usually used in closing the bony defects. 6 In most of the cases, resorption of the graft occurs because of excessive tension in the mucoperiosteum and absence of physiologic stress by the erupting teeth 4 , which ultimately results in inadequate coverage or severe scarring of the palate; 1 But 78.5% of surgeons prefer to do Lefort 1 osteotomy with advancement in patients who had already undergone primary closure of unilateral cleft lip and palate with maxillary hypoplasia.…”
Section: Discussionmentioning
confidence: 99%